Effect of Dietary Intervention Using Low-Carbohydrate Diet to Manage Newly Diagnosed Type 2 Diabetes Mellitus in TUTH Hospital, Nepal (Nepalese Medical Journal, 2021)
Introduction: Low-carbohydrate diet is effective in improving blood glucose parameters, glycated hemoglobin A1c, weight, and waist circumference. The effectiveness of this diet is well accepted in America and the United Kingdom but in Nepal due to many preexisted misbeliefs regarding carbohydrates, we still have a carbohydrate-based diet for type 2 diabetes mellitus.Material and Methods: Fifty-four newly diagnosed type 2 diabetes mellitus without any treatment were selected for solely low-carbohydrate diet intervention (